Implementation of human resource development in Indonesia's super priority tourism destinations - Tandilino, Sari Bandaso (Institute of Computer Science (IOCS), 2024)
The five Super Priority Destinations (DSP) in Indonesia—Lake Toba, Borobudur, Mandalika, Labuan Bajo, and Likupang—are designated National Tourism Strategic Areas with immense potential and unique attractions. However, further development is required to elevate these destinations to the world-class quality of Bali. This research aims to explore how human resource development (HRD) is being implemented across these DSPs to facilitate their growth. Adopting a mixed-method approach, the study conducts qualitative and quantitative analyses through observations, literature reviews, and secondary data. The research's novelty lies in its comprehensive examination of HRD practices simultaneously across all five DSPs, filling a gap in the current literature and providing a unique insight into the strategic development of Indonesia's priority tourism areas